Black pod disease (BPD) of cacao caused by Phytophthora palmivora(Butl.) is one of the major diseases on cacao plantation worldwide. Endophytic fungi (EF), fungi that live asymptomatically inside healthy plants, were examined to study their potentials as biocontrol agent of the disease. Six of EF selected from 37 species (from 2843 isolates), isolated from healthy pods of cacao from Marena in Central Sulawesi were tested for their abilities to control BPD. Pods on living trees in the field were - Tondok, Efi Toding; Sinaga, Meity Suradji; Widodo, ,; Suhartono, Maggy Thenawidjaja (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2012)
Black pod disease (BPD) of cacao caused by Phytophthora palmivora(Butl.) is one of the major diseases on cacao plantation worldwide. Endophytic fungi (EF), fungi that live asymptomatically inside healthy plants, were examined to study their potentials as biocontrol agent of the disease. Six of EF selected from 37 species (from 2843 isolates), isolated from healthy pods of cacao from Marena in Central Sulawesi were tested for their abilities to control BPD. Pods on living trees in the field were sprayed with each EF propagules. The inoculated pods were harvested two weeks later and subsequently inoculated with P. palmivora. Scoring of disease development was performed and quantified as area under disease progress curve (AUDPC). Latent period, infection rate and effectiveness were also recorded. In vitro growth inhibition of pathogen and induced plant defense mechanisms due to EF were also investigated. Xylariaceaeand Calocybe gambosatreatment generated the highest effectiveness control level, i.e. 38.8% and 33.8% respectively, followed by Resinicium friabileand Aschersoniatreatment, i.e. 17.4% dan 12.7% respectively.  Pestalotiopsisand Fusariumwere not effective to control BPD. There was a strong connection between disease severity of BPD with the latent period of pathogen. Growth inhibition of pathogen and induced resistance of plant were partially responsible for disease suppression by Xylariaceae, C. gambosa, R. friabileand Aschersonia. Keywords: Calocybe gambosa, induced resistance, peroxidases, salicylic acid, Xylariaceae